COOPERATION OF THE EDUCATIONAL INSTITUTION WITH EMPLOYERS IN THE EDUCATION OF OF FUTURE CHEFS (Innovative professional education, 2023)
The importance of providing high-quality professional training of competitive, initiative and professionally competent graduates of vocational (professional) education institutions in accordance with the needs of employers is stated. The directions of cooperation between vocational education and trainng institutions and employers in the catering industry are presented.
Keywords: vocational education institution, labor market, employer, cooperation, students